Integrated multiscale assessment of andosol degradation after conversion from grasslands to agriculture - Avilés-Junco, C.; Prado-Pano, B.; Mora-Palomino, L.; Velázquez, A.; Abbruzzini, T.F.; Siebe, C. (Catena (Giessen), 2025)
[Display omitted] •Erosion and slope position shape soil variability, with mid-slopes losing and lower slopes gaining organic matter.•Land use change reduced soil carbon by 29%, exchangeable bases by 36%, and increased bulk density and sand content.•Tillage disrupted andosol’s biogenic structure, reducing microporosity and pore connectivity.•Soil pH and plant-available phosphorous remained unaffected despite intensive fertilization.•Erosion control, reduced tillage, and organic matter inputs are essential to restore Andosols. Andosols, known for their high fertility, are often subject to land use and cover changes (LUC). This study examines the impact of LUC on Andosol properties and functions along a volcanic footslope in the Sierra del Chichinautzin Volcanic Field, south of Mexico City. We selected 11 sites representing continuous oat cultivation (CO), potato-oat annual rotation (POR), and natural grasslands (NG) as controls. An integrated assessment was conducted using soil physical, chemical, and biological indicators, applying a multiscale approach. This included examining soil associations at the landscape level, sampling by genetic horizon at the pedon scale, and performing micromorphological analyses on topsoil aggregates. Compared to NG soils, cropped soils exhibited notable changes: soil carbon (C) stocks decreased from 31 kg m−2 to between 28 and 15 kg m−2, and nitrogen (N) stocks fell from 2.2 kg m−2 to between 2.1 and 1.1 kg m−2. Bulk density in the first 45 cm increased from 0.59-0.65 g cm3 to 0.78–0.86 g cm3, and thesum of exchangeable bases declined by 36 % in the topsoil (from 16 cmolc kg−1 to 10 cmolc kg−1). Additionally, magnesium (Mg) and potassium (K) stocks decreased by 59 % and 72 %, respectively, presumedly due to crop uptake. Soil erosion increased sand content by 23 % and reduced clay and silt contents by 25 % and 14 %, respectively. Agricultural practices disrupted biogenic soil structure and reduced faunal activity significantly. At the landscape scale, LUC primarily affected soil organic matter through erosion and mineralization, impairing essential soil functions suchas fertility, carbon storage, and water infiltration. Implementing erosion control and restoring organic matter—by reducing mechanized tillage, establishing grass strips, terracing, and using cover crops—are essential to preserve these functions.